Prenatal diagnosis of congenital high airway obstruction syndrome - Lago Leal, Víctor Lago; Cortés, Luis Martínez; Del Cacho, Carlos Seco Del (Indian Journal of Radiology and Imaging, 2018)
Congenital high airway obstruction syndrome (CHAOS) is a rare sequence due to a complete obstruction of the fetal airway that blocks the larynx or trachea, either intrinsic atresia or extrinsic compression (e.g., congenital neck mass). Despite the true incidence of CHAOS is unknown, an incidence of 1 per 50,000 newborns is described. If any obstruction occurs in the tracheobronchial airway, this secretion cannot be extricated. Because of this situation, a knock-on effect starts: the enlargement of the lungs squeezes the heart and great veins, what results in a replacement of the heart to the center of the chest becoming small and dysfunctional. Decreased venous return and the failure of cardiovascular system end in ascites and hydrops. The diaphragm planes or inverts according to the severity of the process. In case of unrecognized syndrome during the prenatal period, it usually results in stillbirth or death shortly after delivery. The overall prognosis remains fatal, and long-term medical and surgical challenges for survivors remain considerable even after overcoming fetal intervention.
Keywords: Congenital high airway obstruction syndrome; magnetic resonance imaging; newborn; tracheal agenesis; ultrasound